Exchange Rate Policy and Debt Crises in Emerging Economies - Montiel, Peter (IMF Working Papers; Working Paper ;, 2003)
We explore a model intended to capture the interaction between exchange rate policy, fiscal policy, and outright default on foreign-currency denominated debt. We examine how the exchange rate affects the supply of short-term debt facing the government. We show that under a credible hard peg (currency board), default is a more likely outcome, even without an exceptionally large short-term debt, precisely because a devaluation is not an option. In a more conventional fixed peg, it can be optimal for the government to choose a level of the exchange rate that would be likely to result in partial or complete debt default. Depending on the exchange rate regime, multiple equilibria exist, in one of which the interest rate is high, the exchange rate is overvalued, output is low, and default is high. Under a hard peg, there is a unique equilibrium.